VALIDATION OF SPECTROPHOTOMETRIC METHOD TO QUANTIFY QUERCETIN IN THE IN VITRO DISSOLUTION STUDY OF SELF NANO-EMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) - Wildan Khairi Muhtadi; Ferdy Firmansyah; Tiara Tri Agustini; Pricillia Rahayu; Siti Arifah Fitriyanti; Rodhia Ulfa (Jurnal Farmasi Sains dan Praktis, 2022)
Quercetin possesses low solubility and decreases oral bioavailability. One way to increase the bioavailability of quercetin is by formulating a self-nanoemulsifying drug delivery system (SNEDDS). In vitro dissolution testing of SNEDDS needs to be carried out using a validated analytical method. This study aims to validate the quercetin analytical method in in vitro dissolution testing. Validation was carried out with two solvents, namely hydrochloric acid buffer pH 1.2 (HCl-1,2) and phosphate buffer pH 6.8 (PO-6.8). It tested some parameters, including linearity, detection limit (LoD), quantification limit (LoQ), accuracy, and precision. The quercetin calibration curve for both solvents has a value of r≥0.999. The LoD at HCl-1,2 and PO-6,8 were 0.26 ppm and 0.27 ppm, respectively. The LoQ of HCl-1,2 and PO-6,8 were 0.86 ppm and 0.91 ppm, respectively. The percentage recovery in both solvents was in the range of 80-110%. The relative standard deviation of the two solvents was less than 7.3%. The quercetin analytical method has been successfully validated as indicated by the results of linearity, detection limit, quantification limit, accuracy, and precision that met the requirements